(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Examined in the period, between August 2020 to January 2021 atotal of 97 fishes common carp from one of fish cages from Alforat River in Al-Mussayab city, Babylon, Iraq. These fishes species were examind for Dactylogyrus vastator. Parasites recorded included six species, Dactylogyrus arquatus, D. simlex, D. dogieli, D. minutus, D. extensus, D. vastator. The percentage incidence of infection with the studied Dactylogyrus varied according to different months. The present study included the determination of monthly changes in the main physical and chemical features of the water of River in this study water temperature of water River ranged from 10.4-13.5 Cᵒ, dissolved oxygen from 7.9-9.2 mg/L. PH ranged from 7.0-7.6, salinity ranged from 0.29-0.5/ ppt and the transparency ranged from 58-94 cm. the whole changes in the physical and chemical features of the waters of River were within the normal ranges tolerable by the common carp.